Edukasi Vaksinasi Covid-19 bagi Ibu Hamil dan Nifas (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
Acceptance of the Covid-19 vaccine for pregnant and postpartum women is very low, one of the things that causes it is the lack of information regarding the benefits of the Covid-19 vaccine itself, this causes pregnant and postpartum women not to be vaccinated. The purpose of this community service is conduct counseling related to Covid-19 vaccination education for pregnant and postpartum women. The method of implementing this service is counseling about Covid-19 vaccine education for pregnant and postpartum women, The partners in this service activity are the Kalkubula auxiliary health center in the working area of ??the Biromaru Health Center. The instruments used in this activity are pretest and posttest questionnaires. The average pretest score for 21 pregnant and postpartum women was 40, after education and posttest assessment the average score increased to 70. The conclusion from this activity was that pregnant women and postpartum mothers got better knowledge regarding the Covid-19 vaccination. Suggestions for health workers to further increase education activities for Covid-19 vaccines so that mothers' interest in getting vaccines increases.